RESULTS OF MINI EXTERNAL FIXATOR IN METACARPAL AND PHALANGEAL FRACTURES: Mini External Fixator in Metacarpal And Phalangeal Fractures - Yaseen, Ghulam; Qureshi, Kashif Khursheed; Hussain, Aftab (Pakistan Armed Forces Medical Journal, 2016)
Objective: To evaluate the role of external fixator to treat the soft tissue condition along with metacarpal and phalangeal fracture in terms of fracture union and active range of motion. Study Design: Descriptive, case series. Place and Duration of Study: Department of Orthopedics, Bahawal Victoria Hospital, Bahawalpur from Jun 2011 to May 2013. Subjects and Methods: Total 56 patients of 20-60 years age of both genders with comminuted and open fractures of metacarpal or phalanges bone of the hand, Swanson’s Type-I were included by non-probability, consecutive sampling. Patients with Swanson’s type-2, associated neurovascular injury, intra-articular fractures and fractures with tendon injuries were excluded. In all patients, mini-external fixators were applied and fracture was assessed for union and functional assessment on basis of active range of movement (Excellent, Good, Fair, Poor) at 6th and 12th weeks and 6th month. Results: Mean age was 36.31 ± 8.79 years. Males were 73.21% and remaining 26.79% were females. The most common etiology of fracture was road traffic accident (64.29%) and 69.64% had phalangeal bone fractures. In 76.79% patients, only one digit was fractured while fracture of two and three digits was seen in 16.07% and 7.14% patients respectively. Functional results were excellent in 66.07%, good in 16.07%, fair in 10.71% and poor in of cases. Fracture union was seen in 91.07% at the end of 6 months. Conclusion: This study concluded that mini external fixators are an effective treatment of open fractures of metacarpal or phalanges bone of the hand with high functional outcome and union rates.